2021
DOI: 10.1080/00332747.2021.1940469
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study on the Changes in Mental Health of Healthcare Workers during the COVID-19 Pandemic

Abstract: This study examines Argentinean health care workers in order to 1) test self-perceived job performance levels and the presence of psychological symptoms compatible with common mental disorders, and 2) examine withinperson changes in general discomfort and psychological distress, adjusting for demographic factors, region, and health-related factors during two time points of the COVID-19 pandemic. Method: This longitudinal study comprised 305 healthcare workers who completed a survey at two time points approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
43
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 24 publications
6
43
2
Order By: Relevance
“…Relative to FHCWs with no/minimal distress, those with persistent distress were four times more likely to report prepandemic burnout and more than twice as likely to have had a pre-pandemic psychiatric disorder, which is consistent with the aforementioned study in Argentina (López Steinmetz et al 2021). Those who perceived greater support from leadership and greater emotional support during the acute surge were less likely to have persistent distress symptoms relative to the no/minimal distress group.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Relative to FHCWs with no/minimal distress, those with persistent distress were four times more likely to report prepandemic burnout and more than twice as likely to have had a pre-pandemic psychiatric disorder, which is consistent with the aforementioned study in Argentina (López Steinmetz et al 2021). Those who perceived greater support from leadership and greater emotional support during the acute surge were less likely to have persistent distress symptoms relative to the no/minimal distress group.…”
Section: Discussionsupporting
confidence: 83%
“…Prior studies, including ours, have found that baseline pre-existing psychiatric disorders, burnout, and stress prior to traumatic events are associated with higher likelihood of developing distress in response to a new stressor (Feder et al 2016;Feingold et al 2021;López Steinmetz et al 2021;Smid et al 2012Smid et al , 2013. This finding aligns with studies of disaster responders and survivors, as well as military personnel, which have demonstrated a "stress sensitization" phenomenon in which prior stressors and related distress may result in higher and more persistent post-traumatic distress following exposure to a new traumatic or stressful event (Feder et al 2016;Smid et al 2012Smid et al , 2013.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…As it was suggested by the review of Carmassi et al (2020), based on previous crosssectional and some longitudinal evidence from the Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS) outbreaks, it may be expected to Considering that majority of the healthcare workers in our study were involved in direct patient care, these findings suggest that the frequent exposure to the COVID-19 in their working environment contributes to the uncertainty and suspicion about the contagion, which becomes a heavier factor for the increase of anxiety among them than the actual contagion. Similar hints have emerged with general discomfort and psychological distress outcomes among healthcare workers during the current pandemic (López Steinmetz et al, 2021). During the SARS outbreak, the perception of personal danger, for instance related to shortages of hospital masks, was exacerbated by the uncertainty in healthcare workers (Maunder et al, 2003).…”
Section: Discussionmentioning
confidence: 86%
“…It could be interesting to investigate these differences in perception, which here represented only secondary outcomes, in a study that focuses on them and their expected benefits as the main outcome. Indeed, exposure to chronic stressors and multiple traumatic experiences may generate long-term consequences even after the acute phase of the pandemic, especially for workers in NCH [ 71 , 72 ]. Our study also has several limitations.…”
Section: Discussionmentioning
confidence: 99%